O Valor da Vida e o homicídio para adolescentes em risco psicossocial: avaliação dos níveis de desenvolvimento moral - Borges, Luciana Souza (2011)
We aimed to investigate the judgment of adolescents at psychosocial risk concerning the crime of manslaughter and to ascertain the value they attach to life. We conduct personal interviews, according to the clinical method proposed by Piaget (1947/2005, 1932/1994), with 32 teenagers between 12 and 15 years old, half of each sex, served by two NGOs in the City of Vitoria (ES). From the findings, we found that, with respect to: 1) the characterization of the participants, mostly are attending the Basic Education, have already done paid labor, live with their mother, father and siblings or with their stepfather in their father's place and are linked to a religion, especially the Protestant ones; 2 ) to the true stories of homicides reported by the participants, all have the concept the crime of homicide; about the victims, they reported to know 168 cases, nearly all acquaintances, men, and more than half aged 18 or older; among those who mentioned only one victim or the ones who had to choose only one among the other reported there was a preference for acquaintances or relatives who, in majority, were also men 18 years old or more; there was a tendency of the reason to kill as being illegal drug usage or dealing, or discussions and disagreements in the histories of these murders, which have occurred recently (days, weeks or months) and mostly with firearms; many judged what happened as wrong (value of moral judgement, JVM) mainly because the offender could have done something different, the absence of reason why the victim died and because one should not kill, and with a very low frequency, because of religious reasons, but some assessed as correct because of a consequence of an action of the victim; about the offenders, they presented 107 cases, more often acquaintances, men, and a little more than half aged 18 or older; among those who had already mentioned only one offender or those who needed to choose only one among the others mentioned, we found a preference for acquaintances, who were mostly also men; there was a tendency for the reason to kill as being a consequence of an action of the victim or illegal drug usage or dealing in the stories of these murders; many judged what happened as wrong (JVM) primarily because the offender could have done something different, the lack of reason to kill and because one must not kill, and reduced justifications concerning religious reasons, but a few considered as correct due to the presence of a reason to kill; 3) the fictitious history of murder evaluated by the participants (offender having good or bad reputation), on the JVM, the majority regards the offense committed by the character of ill repute as wrong, because he could have done something different, for the lack of reason to kill or because one should not kill; the same judgment was made toward the aggressor of good repute, with a view that he might have done anything different or could have done something different because of his good reputation, and also because of the lack of reason to kill and religious reasons, very seldom mentioned; about guilt, there was a greater tendency to consider both characters guilty of the crime, since one should not kill, but some thought that neither was to blame because of a consequence of an action of the victim; on the punishment, most felt that the both offenders should be punished because one should not kill, to prevent the crime’s impunity because they could have done something different, besides the religious reasons, though rarely reported; as ways of punishment, most referred to custodial sentences, and in a lower incidence to others like being deprived of something they like and study more, justified on the basis of positive consequence for the offender, because one should not kill, negative consequences for the offender, to avoid negative consequences for the offender and so that the offender could reflect upon his action; as to the time of punishment, many considered a period of more than one month and up to one year and a half or two to four years, for the positive consequence to the offender, the consequence of the bad reputation of the offender, so the offender was be able to reflect on his action and because one must not kill; 4) the fictitious story of murder evaluated by participants (offender being drunk or not), on the JVM, many young people judged the offense committed by the man who was drunk as wrong because he could have done something different, by the consequence of being drunk and because one should not kill, the same judgment was reported with respect to the character who was not drunk, since he could have done something different, because one should not kill and as a result of him not being drunk; about guilt, we found a higher frequency to consider that both offenders are guilty of the crime, since one should not kill, although some have estimated that neither is guilty in view of a consequence of an action of the victim and the presence of a reason to kill; about the punishment, many thought that both offenders should be punished since one should not kill, but some assessed that none of the two should receive punishment because of a consequence of an action of the victim; as ways of punishment, most deemed custodial sentences, and less frequently, others such as community service, to be hospitalized for treatment and to be under house arrest, justifying on the basis justify that one should not kill, to avoid repeat offense within crime, by the characteristics of the offender and so the offender could reflect upon his action; about the time of punishment, most mentioned a period of two to four years, five to ten years and one month to one year, since one should not kill, to prevent repeat offence, by the consequence of the offender being drunk, by the consequence of the offender not being drunk and so the offender was able to reflect on his action; 5) to data in general: there was a tendency to greater appreciation of life, represented by the items offenders could have done something different instead of the homicide, lack of a reason to kill and one should not kill, most often mentioned, and religious reasons, to avoid repeat offence and so the offender could reflect on his action, least incidental; therefore the teenagers lead us supposing that in the context of the homicides (actual or fictitious) discussed in this research, such a crime should not have happened, because it is wrong, considering, overwhelmingly, the value that they gave to life.